Relationship Between Calcium and Vitamin D Level and Bone Stress Fracture in Young Athletes - Ziauddin Khan, Brig. Adnan Anwar, Adnan Afsar, Awais Jameel, Tahir Nawaz, Kamran Sabir, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the association of vitamin D and serum calcium with stress fractures in young athletes. Methods: In this prospective case-control study, we included 160 young athletes who presented to the department of orthopedics, CMH Abbottabad from June-2022 to January-2023. Among those there were 80 patients who presented with stress fractures and 80 patients were those who presented with lower extremity fractures other than stress fractures. Serum calcium and vit. D levels were determined in all patients. Results: Mean age in patients with stress fractures (cases) was 20.3±6.1 years while those in control group was 21.7±8.4 years (p-value 0.22). Mean vit. D levels were significantly lower in cases group; 24.64±11.2 ng/mL versus 30.2±14.7 ng/mL in control group (p-value 0.007). Mean serum PTH levels were no statistically significantly different between the groups; 3.2±1.3 pmol/L versus 3.4±1.7 pmol/L in cases and control group respectively, p-value 0.40. Serum calcium levels in cases were lower; 1.9±0.8 mmol/L in comparison to control group; 2.1±0.7 mmol/L, with p-value 0.01. Conclusion: There is a significant association of serum calcium and vitamin D levels with stress fractures. So regular intake of vitamin D containing foods and milk products should be advised to young athletes to reduce the risk of stress fractures. Keywords: Stress fractures, Athletes, calcium, Vitamin D.